Dante, Domenico, Francesco E Il Crollo Della Basilica Lateranense - Bartoli, Marco (Lateranum, 2023)
The situation of the Church at the beginning of the 13th century was thought to be so serious that the collapse of the cathedral of St. John Lateran could be feared, as is recounted in a famous episode of Dominican and Franciscan hagiographies. A Church that elaborated its high theology in Latin was in danger of no longer knowing how to speak to people who by then were using the vernacular. The essay proposes a rereading of Par XI and XII in this context.